EKULIAH WEBSITE FOR TEACHING WRITING DESCRIPTIVE TEXT DURING THE COVID-19 PANDEMIC SITUATION - Arief Zul Fauzi; Dani Fitria Brilianti (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2021)
The teaching and learning process during the pandemic requires adjustments and the use of adequate learning alternatives in providing material to students in brave classes. This study aims to determine the effectiveness of using the ekuliah website as a learning medium for third semester students in the D-III Accounting study program at Politeknik Harapan Bersama in studying descriptive text material during the COVID-19 pandemic situation. This research is a true experimental study that uses two class groups as research objects. Pre-test was given to both class groups in order to determine the initial competencies possessed by students. The two class groups were then taught descriptive text material with different treatments. The treatment was carried out using the conventional method for the comparison class group and the use of the ekuliah website media for the experimental class group. After the post-test was held at the end of the treatment, the test results experienced a significant increase in the average score for the comparison class group of 2.4 points (mean of pre-test score was 72.6 and post-test was 75) and 6.9 points (mean of pre-test score was 76 and post-test was 82.9) for the experimental class. It can be said that learning descriptive text material for third semester students of the D-III Accounting Study Program at Politeknik Harapan Bersama using the ekuliah website is effective in improving learning outcomes.